PELATIHAN INFORMASI KEARIFAN BUDAYA SEBAGAI WADAH PEMBERDAYAAN SISTEM INFOMASI NAGARI DAN AI - Muhammad Zaim; Hasanuddin WS; Jufrizal; Yetti Zainil; Agustina; Abdurahman; Havid Ardi; Muhammad Al-Hafizh; Ahmad Nusi; Muflihatuz Zakiyah (Komunitas Manajemen Kompetitif, 2025)
Nagari Siguntur, located in Koto XI Tarusan District, Pesisir Selatan Regency, has great potential for cultural tourism. However, information related to the tourism profile, transportation access, infrastructure, and event schedules in the area is still unavailable, even on the official village website, which has led to tourism stagnation. This Community Service Program aims to provide training and assistance in developing digital content about cultural wisdom for the Nagari Siguntur officials as part of the Empowerment Forum for the Village Information System (SINAR) and AI integration. Through this program, the Nagari Siguntur officials are expected to be equipped and ready to establish an AI-assisted Village Information System (SINAR) that provides sufficient public information, thereby accelerating the realization of an independent village in terms of cultural information, with positive impacts on tourism and the local economy. The methods used include training sessions introducing basic concepts of culture and cultural wisdom, cultural content writing, interview techniques, journalistic ethics, and the use of social media platforms for publication, as well as workshops on writing engaging and informative cultural content and managing social media platforms such as websites.